Strengthen the Role of Indonesia in the Constellation of Asean Economic Community Through the Knowledge Based Economy - Muhlisin Muhlisin (Jurnal Hikmatuna, 2015)
The purpose of this paper is to map the role of Indonesia in facing the competition in the era of asean economic community. This idea motivated by a certainty that as a great nation, Indonesia should have a variety of strategies in playing its role to become a nation that has a significant role.The author seeks to explore the roles that can be played by Indonesia in the enforceability of the ASEAN economic community. However, theimplementation of Asean economic community has an implication on the education system in Indonesia. It takes a variety of strategies that should be pursued by the Indonesian government to exist in the competition arena of asean economic community. One of the strategies is to implement knowledge based economy in facing asean economic community. The way to apply it is through good quality of education system, at least the strategy reffers to 4 recommendations from Unesco to the fulfillment of 8 national education standards, because education as a strategic means to establish a characterless human resource. The availability of characterless generation would be one of Indonesia’s strengths and leverages to compete in the era ofAsean Economic Community.